Validity of a motor-cognitive dual-task agility test in elite youth football players - Friebe, D.; Sieland, J.; Both, H.; Giesche, F.; Haser, C.; Hülsdünker, T.; Pfab, F.; Vogt, L.; Banzer, W. (European Journal of Sport Science, 2024)
Agility, as the ability to react rapidly to unforeseen events, is an essential component of football performance. However, existing agility diagnostics often do not reflect the complex motor-cognitive interaction required on the field. Therefore, this study evaluates the criterion and ecological validity of a newly developed motor-cognitive dual-task agility approach in elite youth football players and compare it to a traditional reactive agility test. Twenty-one male youth elite football players (age:17.4 ±0 .6; BMI:23.2 ± 1.8) performed two agility tests (reactive agility, reactive agility with integrated multiple-object-tracking (Dual-Task Agility)) on the SKILLCOURT system. Performance was correlated to motor (sprint, jump), cognitive (executive functions, attention, reaction speed) and football specific tests (Loughborough soccer passing test (LSPT)) as well as indirect game metrics (coaches' rating, playing time). Reactive agility performance showed moderate correlations to attention and choice reaction times (r = 0.48-0.63), as well as to the LSPT (r = 0.51). The dual-task agility test revealed moderate relationships with attention and reaction speed (r = 0.47-0.58), executive functions (r = 0.45-0.63), as well as the game metrics (r = 0.51-0.61). Finally, the dual-task agility test significantly differentiated players based on their coaches' rating and playing time using a median split (p < 0.05; d = 0.8-1.28). Motor-cognitive agility performance in elite youth football players seems to be primarily determined by cognitive functions. The integration of multiple object tracking into reactive agility testing seems to be an ecologically valid approach for performance diagnostics in youth football.